Disciplines of modernity: Archives, histories, anthropologies. - Banerjee, prathama and Mukharji, Projit Bihari (International Center Quarterly)
Author, Saurabh Dube publishers Rutledge, 2023. pp. 105. Price. Rs. 695. 00. -Reproduced